MODERN MARKERS OF INFLAMMATION AND THEIR DIAGNOSTIC SIGNIFICANCE - Akhmedova Sarvinoz (Web of Journals Publishing, 2025)
Inflammation is a complex local vascular-mesenchymal response to tissue damage caused by various agents. Particularly extensive inflammatory processes develop after extensive thermal burns.
Keywords: Inflammation, adhesive molecules, extracellular matrix, soluble mediators, cytokines, fibronectin.